2022
DOI: 10.3390/pharmaceutics14101994
|View full text |Cite
|
Sign up to set email alerts
|

Bruton’s Tyrosine Kinase Inhibitor Zanubrutinib Effectively Modulates Cancer Resistance by Inhibiting Anthracycline Metabolism and Efflux

Abstract: Zanubrutinib (ZAN) is a Bruton’s tyrosine kinase inhibitor recently approved for the treatment of some non-Hodgkin lymphomas. In clinical trials, ZAN is often combined with standard anthracycline (ANT) chemotherapy. Although ANTs are generally effective, drug resistance is a crucial obstacle that leads to treatment discontinuation. This study showed that ZAN counteracts ANT resistance by targeting aldo-keto reductase 1C3 (AKR1C3) and ATP-binding cassette (ABC) transporters. AKR1C3 catalyses the transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In vitro and modeling studies have demonstrated high ABCG2 inhibition by bexarotene and by vemurafenib, a BRAF inhibitor approved for melanoma and used in the treatment of hairy cell leukemia [121]. Cermáková et al reported that zanubrutinib, a second-generation Bruton tyrosine kinase inhibitor approved for relapsed/refractory marginal zone lymphoma (MZL), mantle cell lymphoma (MCL), and Waldenström's macroglobulinemia (WM), counteracts anthracycline resistance by targeting aldo-keto reductase 1C3 (AKR13) and inhibits daunorubicin efflux mediated by ABCB1, ABCC1, and ABCG2, suggesting a possible use in acute myeloid leukemia [122].…”
Section: Abcg2 Reversal: Counteracting Efflux Activitymentioning
confidence: 99%
“…In vitro and modeling studies have demonstrated high ABCG2 inhibition by bexarotene and by vemurafenib, a BRAF inhibitor approved for melanoma and used in the treatment of hairy cell leukemia [121]. Cermáková et al reported that zanubrutinib, a second-generation Bruton tyrosine kinase inhibitor approved for relapsed/refractory marginal zone lymphoma (MZL), mantle cell lymphoma (MCL), and Waldenström's macroglobulinemia (WM), counteracts anthracycline resistance by targeting aldo-keto reductase 1C3 (AKR13) and inhibits daunorubicin efflux mediated by ABCB1, ABCC1, and ABCG2, suggesting a possible use in acute myeloid leukemia [122].…”
Section: Abcg2 Reversal: Counteracting Efflux Activitymentioning
confidence: 99%
“…Among the reductases, AKR1C3 is the most active enzyme, with a confirmed role in ANT resistance . Valuable experiments have shown that inhibition of the AKR1C3-catalyzed metabolism of DAU leads to an increase in the efficacy of DAU against cancer cells and sheds light on the possible potential to reverse ANT resistance. In triple-negative breast cancer (TNBC), AKR1C3 expression has been shown to be associated with reduced sensitivity to doxorubicin (DOX) . Upregulation of AKR1C3 expression is thought to be one of the key factors in MCF-7 breast cancer cells resistance to DOX .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pharmaceutical studies on AKR1C3 have been reported over the past decades. Representative AKR1C3 inhibitors can be divided into (1) cyclopentane derivatives and analogues of estrogen lactone steroids; (2) natural products such as flavonoids, cinnamic acids, and alkaloids; (3) benzodiazepines; (4) nonsteroidal anti-inflammatory drugs (NSAIDs); (5) specific AKR1C3 inhibitors harboring distinct chemotypes, such as SN3363840, coumarin derivatives, and bifunctional naphthyl derivatives; (6) off-label use compounds, such as cyclin-dependent kinase (CDK) inhibitors, , class I phosphoinositide 3-kinase (PI3K) inhibitor Buparlisib, Bruton’s tyrosine kinase (BTK) inhibitors, , poly (ADP-ribose) polymerase inhibitor Olaparib, and isocitrate dehydrogenase 2 inhibitor enasidenib . As per our knowledge to date, no specific AKR1C3 inhibitor has been successfully marketed for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Improved cancer outcomes are possible through the use of novel medications and tumor-specific delivery of FDA-approved anticancer treatments [4]. Some of the derivatives [indole-3-pyrazole-5-carboxamide analogues (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)] had anticancer effects against cancer cell lines that were comparable to or superior to those of sorafenib. With IC 50 values ranging from 0.6 to 2.9 M, compound 18 demonstrated strong activity against the HCC cell lines [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some drug classes of the phenoxy group have been discovered and are currently being utilized in therapy as anti-cancer drugs like Zanubrutinib, under the brand name Brukinsa. It is used to treat the cancers mantle cell lymphoma (MCL), Waldenstrom's macroglobulinemia (WM), marginal zone lymphoma (MZL), and chronic lymphocytic leukaemia (CLL) [13]. Moreover, Ibrutinib is a small molecule that acts as an irreversible potent inhibitor of Burton's tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%